Coordenação de estudos clínicos na CUF Academic Center - Melo, Francisca Baptista Vieira (2022)
ABSTRACT This report was carried out in order to obtain the master's degree in clinical investigation management. The internship took place at the CUF Academic Center, in two hospital units, Hospital CUF Descobertas and Hospital CUF Tejo. In this internship, it was possible to develop and accomplish coordination activities of clinical studies. This report is divided into two parts: Part I: presents a literature review that attempts to answer the question "What is the economic contribution of clinical trials to national economy?". The direct and indirect impacts that this activity may have on the economy and sustainability of the SNS is analyzed. Part II: description of the activities carried out during the internship. There is an overview of the objectives, a brief description of the host institution and a detailed exposition of the activities. Afterwards, it is elaborated a critical discussion of the internship and a SWOT analysis to define, more specifically, which action should be followed in the future to improve clinical research investigation in the units where the internship took place. The conclusion of this report provides the most significant finds in the scientific literature and the objectives, tasks and learnings accomplished, moreover its impact on this masters.